Women's ritual in China : Jiezhu (receiving Buddhist prayer beads) performed by menopausal women in Ninghua, western Fujian. - Cheung, Neky Tak-ching (Edwin Mellen Press, 2008)
Based on historical, textual, and field studies, this work examines the paradoxical nature of jiezhu, which simultaneously upholds and challenges tradition through religious and social empowerment. Jiezhu delivers the woman into a new phase of being by first providing private meanings to her. Ritual acts can bridge memory and imagination. The ritual program allows the woman to go back and forth between the past, the present and the future. Jiezhu dramatically juxtaposes girlhood and mature womanhood, reenacts her wedding and rehearses her future funeral. Death and rebirth symbols abound. In jiezhu, the woman 'witnesses' her own funerary rites to ensure abundant personal possessions are burned for her to receive in the underworld after her death. The woman acquires spiritual strength to ease her menopausal stress and to allay the fears of the approach of death. Jiezhu and Amituofo recitation make up a twin tool to ensure a more fortunate rebirth. Second, jiezhu gives social meanings. The woman is given a new identity. She is now eligible for Amituofo recitation and becomes a member of the nianfo community. As social inferiority can be compensated for by a show of lavishness, jiezhu as an expensive event creates symbolic capital. Jiezhu has become a symbol of prestige and resources that in part enhances the status of the women. The women are also able to express their power within the limits of their traditional politics. The woman's contributions as a wife and a mother are valued and celebrated in the jiezhu ceremony. The youthful, bright and colorful gift items given by the married daughter display a defiant tone against the association of jiezhu with old age. Jiezhu celebrates an oft-neglected life crisis of women. To conclude, jiezhu on the one hand 'traditionalizes', and on the other hand, as a strategic mode of action, challenges traditions through religious and social empowerment. Jiezhu preserves the established order but it also facilitates transforma -- Présentation de l'éditeur.